Impact of Sn-Doped Zn3P2 Nanopowders: Structural, Optical, and Photoluminescence Studies - Nakka Praveenkumar; Nasina Madhusudhana Rao; Mathew K. Moodley; S.V. Motloung Setumo (Sustainable Chemical Engineering, 2026)
A solid-state method was used to create diluted magnetic semiconductor nanoparticles doped with Sn. These nanoparticles have the formula Zn3-xSnxP2 , where x = 0.03, 0.05, and 0.09. The impact of Sn-dopant concentration on the optical, photoluminescent, and structural characteristics of artificial samples was investigated. The samples were created with a tetragonal structure, according to the X-ray diffraction study, and the diffraction peaks showed no additional Sn or impurities. As the Sn concentration rose, the lattice parameters changed from a = b = 8.1093 to 8.1431 Å and c = 11.1193 Å to 11.1398 Å. As the dopant level increased, the nanoparticles tended to clump together in the 500 nm region, according to scanning electron microscope images. The energy-dispersive X-ray spectroscopy study indicates that this dopant concentration is close to the required Sn, P, and Zn atomic ratios. UV-visible-near-infrared spectroscopy and photoluminescence tests were used to study the optical characteristics. With an increase in Sn concentration, the optical band gap grew from 1.422 eV to 1.432 eV. The examination of photoluminescence revealed emissions in the blue, violet, and ultraviolet bands.